SAT0242 Therapeutic Response to TOCILIZUMAB in Rheumatoid Arthritis: Does Body Weight Have an Influence?. (10th June 2014) - Segaud, N.; Haffner, C.; Philippe, P.; Deprez, X.; Houvenagel, E.; Coquerel, P.; Cortet, B.; Flipo, R.-M.
Abstract : Background: The adipose tissue belongs to the endocrine metabolic system which impacts inflammatory events in rheumatoid arthritis (RA). Recently a few studies have demonstrated that the body weight and Body Mass Index (BMI) are predictive factors of the clinical response of patients treated for RA by Infliximab. Moreover others studies proved that Obesity has also been associated with the increased incidence and a worse outcome of RA. Objectives: The purpose of this study was to assess the influence of the body weight on the therapeutic response and the remission rate after one year of treatment with TOCILIZUMAB in RA. Methods: This retrospective multicenter longitudinal study included patients treated by TOCILIZUMAB (8mg/kg per 4 weeks) for RA for at least one year from 2006 onwards. Patients for whom the body height was known were specifically analysed to test the influence of BMI and categories of BMI (normal<25, overweight: 25-30 and obesity >30kg/m 2 ). After one year, of treatment the therapeutic response was estimated by the variation of the DAS 28 score. Linear regression of the delta DAS 28 according to initial body weight and secondarily to the BMI was performed. EULAR response and remission rates were assessed according to body weight and to the BMI. Two definitions of remission were admitted: DAS 28 score <2, 6 or the new Boolean remission. Results: A total of 129 patients were included. At treatment initiation, patients had an average weight of 71, 6±17, 6 kg and an average DAS 28 5, 4±1, 3. At the endpoint, the DAS 28 score was 2, 1±1, 2. Linear regression showed a positive impact of body weight on DAS 28 improvement (p=0, 0261, Fig. 1 ). According to EULAR classification 4 patients were in good therapeutic response, 120 in moderate response and 5 had no response without statistically correlation with body weight (p=0, 7). Of the 101 patients in remission with a DAS 28 score <2, 6 after a year of treatment, the average weight was 72, 3±18, 6 kg versus 69, 2±15, 2 kg for the patients who were not in remission, but this is not statistically significant (p=0, 4). Only 13 patients were in Boolean remission. When comparing the patients in the group above the median of weight (70kg) and those below the median, Delta Das 28 showed a strong tendency to be higher for the heaviest patients, respectively 3, 6±1, 6 and 3, 1±1, 4 (p=0, 0519). No statistical difference was found regarding remission. With regard to the 104 patients of whom body height was known, the average BMI was 26, 9±6, 3 kg/m 2 with an initial DAS 28 5, 5±1, 3 and final DAS 28 3, 4±1, 5. Linear regression of Delta Das 28 positively correlated with the initial BMI (p=0, 0144). 96 patients presented a good response, 4 patients were in moderate response and 4 had no response. 80 patients obtained a final DAS 28 <2, 6 and 9 patients a Boolean remission. A total of 44 patients were in the normal BMI group, 34 were overweight and 26 were in the obese group. Patients in the obese group improved their Das 28 by 4, 1±1, 3 versus 3, 0±1, 2 for normal BMI and 3, 2±1, 7 and overweight (p=0, 0087/Fig. 2 ). There was no statistically difference for remission. Conclusions: This study suggests a positive influence of the high initial body weight and high BMI on the improvement of the DAS 28 in patients treated with TCZ in RA. Acknowledgements: Grant to Roche-Chugai Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3855